PSYCHOLOGICAL ADJUSTMENT OF THE DRIVER AND FORMALIZATION (Municipal economy of cities. Series: «Economy science», 2013)
Consider the psychological adjustment of the driver’s impact on the relationship between the motivation of the driver and its purpose. The purpose of the driver has been described by the set of characteristics insult goal. The mathematical formulation of the objective function purpose of the driver.